A minimal structural variation can overcome tumour resistance of oxaliplatin: the case of 4, 5-dehydrogenation of the cyclohexane ring. Issue 56 (11th October 2019) - Papadia, Paride; Gandin, Valentina; Barbanente, Alessandra; Ruello, Alessandro G.; Marzano, Cristina; Micoli, Katia; Hoeschele, James D.; Natile, Giovanni; Margiotta, Nicola
Abstract : A new family of anticancer compounds has been derived from oxaliplatin by inserting a double-bond between carbons 4 and 5 of the 1, 2-diaminocyclohexane ring. Abstract : A new family of anticancer compounds has been derived from oxaliplatin by inserting a double-bond between carbons 4 and 5 of the 1, 2-diaminocyclohexane ring. Testing against a panel of human tumour cell lines including cervical (A431), ovarian (2008), and colon carcinomas (HCT-15 and LoVo), and two oxaliplatin-resistant clones (LoVo OXP and LoVo MDR) has shown that the new compounds have, in general, equal if not better cytotoxic activity and are able to overcome the oxaliplatin-resistance. Moreover, the oxalato derivative induced lipid droplets increase in LoVo OXP cells thus suggesting the involvement of metabolism stress in its mechanism of action.